1997
DOI: 10.1007/bf01294727
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical study of catecholaminergic neurons in the senescence-accelerated mouse (SAM-P8) brain

Abstract: The catecholaminergic neurons of senescence-accelerated mice (SAM-P8) were analyzed by immunohistochemical microphotometry in terms of immunoreactivities to aromatic L-amino acid decarboxylase (AADC), dopamine (DA), or noradrenaline (NA). Accelerated senescence-resistant mice (SAM-R1) were used as control mice. The immunoreactivities to AADC, DA, and NA of the catecholaminergic neurons of the SAM-P8 mice were weaker than those of the SAM-R1 mice in all the brain regions. Immunoelectron microscopy revealed prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Recently, Zhu et al [45] revealed using the methods of histological silver staining and TUNEL that some Purkinje cells in the medial cerebellum and the vermis appeared to disappear during aging in SAMP8 mice, consistent with the findings in Alzheimer brains [46,47] . d. Other findings: In addition, an immunohistochemical study by Karasawa et al revealed that dopamine neurons in the substantia nigra and noradrenaline neurons in the locus coeruleus degenerated more rapidly during aging in SAMP8 mice than in control SAMR1 mice [48]. On the other hand, Tanaka et al [49] investigated the changes in oligodendrocytes in the brains of SAMP8 mice using immunohistochemistry for myelin basic protein (MBP) and 2 0 3 0 -cyclic nucleotide 3 0 -phosphodiesterase (CNP) as the oligodendrocyte markers.…”
Section: Neuropathological Studiesmentioning
confidence: 93%
“…Recently, Zhu et al [45] revealed using the methods of histological silver staining and TUNEL that some Purkinje cells in the medial cerebellum and the vermis appeared to disappear during aging in SAMP8 mice, consistent with the findings in Alzheimer brains [46,47] . d. Other findings: In addition, an immunohistochemical study by Karasawa et al revealed that dopamine neurons in the substantia nigra and noradrenaline neurons in the locus coeruleus degenerated more rapidly during aging in SAMP8 mice than in control SAMR1 mice [48]. On the other hand, Tanaka et al [49] investigated the changes in oligodendrocytes in the brains of SAMP8 mice using immunohistochemistry for myelin basic protein (MBP) and 2 0 3 0 -cyclic nucleotide 3 0 -phosphodiesterase (CNP) as the oligodendrocyte markers.…”
Section: Neuropathological Studiesmentioning
confidence: 93%
“…Reports on 5-HT neurons have described the regional specificity of degeneration [6,17]. We have previously reported decrease in IR-Is and morphological change to DA neurons in aged SAMP8 [4] and noted the sensitivity of DA neurons to an inhibitor of monoamine synthesis. Tetrahydrobiopterin (BH4) is a coenzyme of both TH and tryptophan hydroxylase (TrH), the rate-limiting enzymes in catecholamine and indolamine syntheses, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported decreased immunoreactive intensity (IR-Is) and morphological changes in dopaminergic (DA) neurons in senescenceaccelerated mouse-prone (SAMP8) mice [4]. Regarding the changes in monoamine synthesis in relation to aging, we have also reported the sensitivity of CA neurons to inhibitor of monoamine synthesis [5].…”
Section: Introductionmentioning
confidence: 94%
“…However, there is a decrease in the number of dopamine (DA) neurons and the associated ultrastructural changes in the neurons of the nigrostriatal system in SAMP8 as compared with SAMR1. This reduction is even greater in aged SAMP8 mice (8-10 months old) (Karasawa et al, 1997), suggesting a reduced DA level in SAMP8 worsened by age. The administration of 2,4-diamino-6-hydroxypyrimidine (DAHP), an inhibitor of GTP cyclohydrolase I, to inhibit DA and serotonin syntheses in young mice (2 months old) and aged mice (10 months old), revealed that DA turnover is lower in aged mice than in young mice (Karasawa et al, 1999).…”
Section: Chemokine Receptorsmentioning
confidence: 97%